2017
DOI: 10.1136/bmjoq-2017-000145
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the WHO Safe Childbirth Checklist: lessons learnt on a quality improvement initiative to improve mother and newborn care at Gobabis District Hospital, Namibia

Abstract: BackgroundAlthough there are many evidence-based practices that reduce the risk of maternal and neonatal mortality around the time of birth, there remains a gap between what is known and the care received. This know-do gap is a source of preventable maternal and perinatal deaths and is the focus of improvement efforts in many countries. Following an increase in perinatal and maternal deaths, Gobabis District Hospital initiated a quality improvement (QI) initiative to increase adherence to these WHO Safe Childb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
70
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 9 publications
4
70
1
5
Order By: Relevance
“…First, the WHO developed the Safe Childbirth Checklist which includes 29 EBPs that focus on maternal and neonatal outcomes at four pause points – on admission to the facility, at the time of pushing (or before cesarean delivery), soon after birth (within 1 h) and at discharge. This checklist has been used in a variety of LMICs contexts, including India, Sri Lanka, and Namibia [911]. In Namibia, the authors reported an increase of EBPs from 68% to 95% over a 6-month period, as well as a reduction in perinatal mortality from 22 to 13.8 deaths/1000 deliveries [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the WHO developed the Safe Childbirth Checklist which includes 29 EBPs that focus on maternal and neonatal outcomes at four pause points – on admission to the facility, at the time of pushing (or before cesarean delivery), soon after birth (within 1 h) and at discharge. This checklist has been used in a variety of LMICs contexts, including India, Sri Lanka, and Namibia [911]. In Namibia, the authors reported an increase of EBPs from 68% to 95% over a 6-month period, as well as a reduction in perinatal mortality from 22 to 13.8 deaths/1000 deliveries [11].…”
Section: Introductionmentioning
confidence: 99%
“…This checklist has been used in a variety of LMICs contexts, including India, Sri Lanka, and Namibia [911]. In Namibia, the authors reported an increase of EBPs from 68% to 95% over a 6-month period, as well as a reduction in perinatal mortality from 22 to 13.8 deaths/1000 deliveries [11]. A more recent report from the Better Birth Trial in India revealed that despite an increase in use of EBPs, outcomes did not improve [12], suggesting that the checklist alone may be insufficient in some contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is also clear that training is not adequate because performance suffers from a know-do gap: health worker knowledge of correct protocol is often well above performance [16,17,18,19,6,20]. However, knowing that a knowdo gap exists does not help us know how to close the gap.…”
Section: Introductionmentioning
confidence: 99%
“…The SCC is organized to drive change at four critical moments (or pause points): on admission, before delivery, within 1 hour after delivery, and before discharge. Initial studies have demonstrated an association between SCC use and improved adherence to EBPs …”
Section: Introductionmentioning
confidence: 99%
“…Initial studies have demonstrated an association between SCC use and improved adherence to EBPs. [9][10][11] Evidence from quality-improvement initiatives has shown the importance of integrated interventions to change both provider behavior and the healthcare system. When done well, supportive supervision, clinical mentorship, and coaching can be effective in changing provider behavior in a variety of settings, increasing the rate of skill transfer or adoption and generating more sustained improvement in performance than training alone.…”
Section: Introductionmentioning
confidence: 99%